The Kruppel-like zinc-finger gene ZNF236 is alternatively spliced and excluded as susceptibility gene for diabetic nephropathy - Halama, Niels; Breedijk, Annette; Vardarli, Irfan; Akkoyun, Imren; Yard, Benito A.; Janssen, Bart; Woude, Fokko J. van der (Genomics, 2003)
Diabetic nephropathy (DN) is the most common cause of renal failure in the western hemisphere. Epidemiological studies have suggested a genetic susceptibility for DN. Linkage analysis showed evidence for a locus on chromosome 18q22.3-q23 in Turkish families. We report the construction of a transcript map of the target region on chromosome 18q22.3-q23 and analysis of the candidate gene ZNF236. By using recent publications, human genome databases, and a multitude of available protein-predicting programs, we obtained a detailed map of this 4.7-Mb-spanning region. We sequenced ZNF236 in patients with diabetic nephropathy and diabetes without nephropathy, as well as in unaffected controls. We observed multiple splice forms in all individuals but no mutation in any of the patients. It seems improbable, therefore, that ZNF236 is a gene that confers DN susceptibility.